Climate analogues: finding tomorrow’s agriculture today - Harvey, Blane; Ensor, Jonathan; Carlile, Liz; Garside, Ben; Patterson, Zachary; Naess, Lars Otto (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
“Climate Analogues: Finding Tomorrow’s Agriculture Today” is an effort by CCAFS to make climate change adaptation a more tangible endeavour by encouraging the exchange of knowledge between communities. The idea is that the “analogues tool” helps to identify geographic areas where growing conditions today mirror future climates. Then to promote exchanges between the communities living in these areas so that learning can take place on agriculture practices that work well in those “future” climates and encourage discussion on how these practices can be adapted to local context to cope with potentially dramatic shifts in growing conditions over time.